Analysis of the Influence of Students' Perceptions of Parental Assistance on the Internalization of Students' Moral Attitudes in Class VII Islamic Education Learning at SMP Muhammadiyah 8 Cakru - Ramadhaniameliyah Safitri; Sofyan Rofi; Hairul Huda (Jurnal Studi Guru dan Pembelajaran, 2026)
This research is motivated by the phenomenon of declining discipline and social ethics among students, as well as the importance of the synergy within the "Triple Center of Education" (Tripusat Pendidikan) in character building. Objective: The primary objective of this study is to identify and analyze the significant influence of students' perceptions of parental guidance on their moral behavior (akhlak) within Islamic Education (PAI) learning, specifically focusing on the Aqidah Akhlak (Creed and Morals) element. Methodology: This study employed a quantitative approach with a causal associative design. The population consisted of all 7th-grade students at SMP Muhammadiyah 8 Cakru, with a sample size of 58 respondents. Data collection was conducted through observation and the distribution of questionnaires, which had been tested for validity and reliability. Data analysis techniques included prerequisite tests (normality and linearity) and parametric statistical analysis using SPSS version 22 software. Results: The findings indicate a positive and significant influence of students' perceptions of parental guidance on their moral attitudes. This is evidenced by the linearity test results, showing a significance value of 0.000 (p < 0.05) and an F-count of 52.24. These findings suggest that a more positive student perception of parental guidance encompassing the creation of an Islamic atmosphere, exemplary behavior (modeling), discipline, and psychological support correlates with higher quality in students' moral behavior. Conclusion: This study concludes that parental guidance serves as an effective behavioral modeling tool in internalizing the values of akhlakul karimah (noble character) into the students' personalities.